Eating behaviour, physical activity and mental health by COVID - 19 quarantine in older adults in Trujillo - Cruzado Joaquin, Analy (2023)
Introduction: The COVID-19 pandemic led to a quarantine in Peru seeking the greatest social distancing. Objective: To determine the effect of quarantine on eating behavior, physical activity and mental health before and during this period in older adults in Trujillo. Study: Observational, descriptive, longitudinal in 350 older adults, by means of virtual survey on frequency of food consumption, physical activity and changes in mental health, analyzed by chi-square. Findings: The intake of alcoholic beverages and fast food decreased. The level of physical activity decreased significantly. Feelings of loneliness, depression, anxiety, among others, increased. Perception of weight gain and waist size increase was found. Conclusions: COVID-19 quarantine in older adults decreased physical activity, affected mental health and gave perception of weight and waist size increase, without affecting eating behavior.